Sistem Informasi Terintegrasi Pengelolaan Catatan Kasus Konseling Siswa menggunakan User-Centered Design - Mardhia, Murein Miksa; Aretama, Lucky Barga; Khusna, Arfiani Nur; Perwira, Luqman Tifa; Prakasa, Anabela Aji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Deviant behavior in adolescents is a significant issue in education, particularly in the field of Guidance and Counseling (BK). The paper-based manual recording system makes it difficult for BK teachers to manage data such as case histories, counseling reports, and attendance. This study aims to develop a website-based BK information system using the User-Centered Design (UCD) approach and the Waterfall method. Data was collected through interviews and observations of BK teachers, followed by designing a user-friendly interface, system development, and testing. This system enables BK teachers to manage student data efficiently and allows principals to monitor reports in real time. The results of the System Usability Scale test showed an average score of 80.75 (category B, Good), and the Blackbox test showed appropriate functionality. The system proved effective, efficient, and met user needs in managing BK services in schools thus enabling BK teachers to focus more on quality counseling with data-based decision making.